2019
DOI: 10.21273/hortsci13961-19
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza and Plant Growth-promoting Bacteria Alleviate Drought Stress in Walnut

Abstract: Additional index word. Azotobacter chroococcum, Glomus etunicatum, nutrient acquisition, peroxidase activity, proline, symbiotic bacteria Abstract. Drought stress is one of the main constraints limiting worldwide crop production. Arbuscular mycorrhizae (AM) and plant growth-promoting bacteria (PGPB) such as Azotobacter chroococcum and Azospirillium lipofrum have been shown to alleviate drought stress effects. Therefore, the interaction effect of AM fungi [Glomus mosseae, G. etunicatum, and a mix of these (G. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 32 publications
3
47
0
2
Order By: Relevance
“…Nutrient distribution and accumulation are results of the interaction between plant and environmental factors and reflect not only the adaptability of plants to environmental factors, but also the impact of the environment on plants [89]. Previous studies suggested that the promotion of nutrient uptake by AMF is an important physiological mechanism of the mycorrhiza-induced drought resistance of the host plant [2,7]. Yang et al [8] discovered that black locust seedlings inoculated with F. mosseae and R. intraradices had enhanced leaf C, N, and P concentrations under both WW and drought stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient distribution and accumulation are results of the interaction between plant and environmental factors and reflect not only the adaptability of plants to environmental factors, but also the impact of the environment on plants [89]. Previous studies suggested that the promotion of nutrient uptake by AMF is an important physiological mechanism of the mycorrhiza-induced drought resistance of the host plant [2,7]. Yang et al [8] discovered that black locust seedlings inoculated with F. mosseae and R. intraradices had enhanced leaf C, N, and P concentrations under both WW and drought stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Drought is one of the most important factors affecting plant growth in terrestrial ecosystems [1]. Climate change increases the odds of severe drought conditions around the world [2,3]. Drought stress can change plant water status, and has obvious effects on seed germination, plant morphological structure, biomass distribution, soil nutrient availability, photosynthesis, and metabolism, thereby seriously restricting the normal growth, development, survival, and productivity of plants [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a single inoculation treatment, dual inoculation with AMF and Nitroxin resulted in a higher N content. Several studies have shown that improving the uptake of nutrients using AMF and rhizobacteria is a basic mechanism for improving the adverse effects of drought stress in plant development [20,63].…”
Section: Plos Onementioning
confidence: 99%
“…The walnut tree has a high-water demand, so its production and tree growth can be influenced by soil drought stress (Vahdati et al, 2009). Behrooz et al (2019) tried to use G. mosseae, G. etunicatum, and a mixture of both inoculated into one-year-old J. regia cv. 'Chandler' seedlings, and found that these AMF species significantly improved the contents of some metabolites under drought stress, such as total phenolic, proline, total soluble sugar, and starch, and also enhanced activities of peroxidase.…”
Section: Enhancement Of Drought Tolerancementioning
confidence: 99%
“…The stimulated nutrient acquisition also was found in drought-stressed walnut plants after AMF inoculation. G. mosseae, G. etunicatum, and the mix of both collectively increased leaf N, P, and Zn contents of walnut under normal water and drought stress conditions (Behrooz et al, 2019). In Juglans regia L. Liaohe 1, Huang et al (2020) used five AMF species (A. scrobiculata, D. spurca, G. etunicatum, G. mosseae, and G. versiforme) and found that the AMF inoculations could improve plant growth performance, dependent on AMF species.…”
Section: Introductionmentioning
confidence: 99%